Analysis of Factors that Influence Jamu Micro Business Income - Aditya, Finky (Efficient: Indonesian Journal of Development Economics, 2020)
The purpose of this study was to determine the owners that influence Semarang's jamu microbusiness income. This research used a quantitative method with a population of jamu microbusiness in Semarang City. The sampling technique used in this study was random sampling technique. Data analysis used multiple linear regression with SPSS Program version 21, where the variables used include capital (X1), labor (X2), marketing strategies (X3), technology (X4) on income (Y). The results of the multiple linear regression analysis showed capital (X1), labor (X2), marketing strategy (X3) and technology had a positive and significant effect on the income (Y) jamu microbusiness in Semarang City. The conclusion of this research is that the better capital, labor, marketing strategies and technology will affect the perception of an increase in the income of jamu microbusiness in Semarang City. Suggestions for jamu business owners who are already running or developing should pay attention to fowners such as capital, labor, marketing strategies and technology. Tujuan dari penelitian ini adalah untuk mengetahui pemilik yang mempengaruhi pendapatan usaha mikro jamu Semarang. Penelitian ini menggunakan metode kuantitatif dengan populasi usaha mikro jamu di Kota Semarang. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah teknik random sampling. Analisis data menggunakan regresi linier berganda dengan Program SPSS versi 21, di mana variabel yang digunakan meliputi modal (X1), tenaga kerja (X2), strategi pemasaran (X3), teknologi (X4) pada pendapatan (Y). Hasil analisis regresi linier berganda menunjukkan modal (X1), tenaga kerja (X2), strategi pemasaran (X3) dan teknologi memiliki pengaruh positif dan signifikan terhadap pendapatan (Y) usaha mikro jamu di Kota Semarang. Kesimpulan dari penelitian ini adalah bahwa modal, tenaga kerja, strategi pemasaran dan teknologi yang lebih baik akan mempengaruhi persepsi peningkatan pendapatan usaha mikro jamu di Kota Semarang. Saran untuk pemilik bisnis jamu yang sudah berjalan atau berkembang harus memperhatikan pemilik seperti modal, tenaga kerja, strategi pemasaran dan teknologi.